2021
DOI: 10.1136/jclinpath-2021-207640
|View full text |Cite
|
Sign up to set email alerts
|

Fostering intrinsic motivation in remote undergraduate histopathology education

Abstract: AimsThe levels of abstraction, vast vocabulary and high cognitive load present significant challenges in undergraduate histopathology education. Self-determination theory describes three psychological needs which promote intrinsic motivation. This paper describes, evaluates and justifies a remotely conducted, post-COVID-19 histopathology placement designed to foster intrinsic motivation.Methods90 fourth-year medical students took part in combined synchronous and asynchronous remote placements integrating virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
8
0
3
Order By: Relevance
“…In fact, on one occasion, when the teaching staff were delayed due to a timetabling error, instructors arrived 10 min into the session to find all students engaged in the task, having begun generating their e‐workbook using the lecture slides as a guide. This indeed aligns to the literature where it was observed that the integration of VM into histology teaching increased student collaboration (Braun & Kearns, 2008 ; Telang et al, 2016 ; Triola & Holloway, 2011 ; Uraiby et al, 2021 ). The social, academic and psychological benefits of collaborative learning are widely stated in the literature and include higher productivity, engagement and achievement (Hurst et al, 2013 ; Laal & Ghodsi, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…In fact, on one occasion, when the teaching staff were delayed due to a timetabling error, instructors arrived 10 min into the session to find all students engaged in the task, having begun generating their e‐workbook using the lecture slides as a guide. This indeed aligns to the literature where it was observed that the integration of VM into histology teaching increased student collaboration (Braun & Kearns, 2008 ; Telang et al, 2016 ; Triola & Holloway, 2011 ; Uraiby et al, 2021 ). The social, academic and psychological benefits of collaborative learning are widely stated in the literature and include higher productivity, engagement and achievement (Hurst et al, 2013 ; Laal & Ghodsi, 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Alguns desafios do ensino remoto foram mencionados nos artigos pesquisados, principalmente ao buscarem contornar os aspectos negativos que a modalidade trouxe. As principais dificuldades citadas estavam relacionadas aos seguintes aspectos: as estratégias para adaptar as aulas práticas ao ensino remoto 8,[12][13][14][27][28][29][30][31][32][33][34][35][36] , os desafios tecnológicos 15,20,34,[37][38][39] e a adequação brusca ao contexto on-line 8,25,34,[40][41][42] .…”
Section: Resultsunclassified
“…Isso pode ser relacionado diretamente com o fato de o curso de Medicina ter uma grande carga horária e requisitar um contato frequente dos estudantes com os pacientes, imprescindível para a construção do conhecimento a partir da experimentação das vivências 75 . Além disso, como o modo de abordagem mais frequentemente observado nos artigos foi o totalmente remoto 8,9,[14][15][16][17][22][23][24][25][26][27][28]31,32,35,36,38,39,[41][42][43][44][45][46][50][51][52][53][54][55][56][57][58][59][60][61]63,67,68,72,[78][79][80] , pode-se assumir que não foi possível, para as instituições relacionadas aos artigos recuperados, elaborar estratégias para tentar suprir ou contornar essa adversidade. Todavia, os poucos cursos capazes de manter algumas atividades práticas utilizaram estratégias como a diminuição do número de alunos por aula, por meio da formação de pequenas turmas…”
Section: Discussionunclassified
“…Postsecondary students who do not exercise SD are at risk for dependency on others, such as their parents, teachers, and peers [ 22 , 26 ]. Similarly, postsecondary students may feel disempowered, dissatisfied, and unmotivated due to the COVID-19-related restrictions on daily life [ 9 , 18 , 19 , 20 , 66 , 67 ]. Many of the daily decisions are being made for postsecondary students by institutional administrators, which may cause students to experience paternalism and lack of autonomy [ 19 , 67 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Although concept analyses focusing on SD have been previously published [ 35 , 42 ], none have explored the concept of SD with special attention to COVID-19 as it applies to post-secondary students. Despite of research on how SDT applies to motivating learning in this population during the COVID-19 pandemic [ 51 , 66 , 71 , 72 ], there is limited information applying this concept to pandemic-related psychological distress. This manuscript adds to the current body of knowledge by making connections between several phenomena that are potentially related to SD and impacted by the pandemic, such as psychological distress, autonomy, and resilience.…”
Section: Discussionmentioning
confidence: 99%